2013
DOI: 10.1051/e3sconf/20130129004
|View full text |Cite
|
Sign up to set email alerts
|

Looking for biomarkers of Hg exposure by transcriptome analysis in the aquatic plantElodea nuttallii

Abstract: Abstract.Recently developed genomics tools have a promising potential to identify early biomarkers of exposure to toxicants. In the present work we used transcriptome analysis (RNA-seq) of Elodea nuttallii -an invasive rooted macrophyte that is able to accumulate large amounts of metals-to identify biomarkers of Hg exposure. RNA-seq allowed identification of genes affected by Hg exposure and also unraveled plant response to the toxic metal: a change in energy/reserve metabolism caused by the inhibition of phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that mRNA abundance profiles of two or more contrast conditions or biological states can be potentially developed as biomarkers (Riedmaier and Pfaffl, 2013) for early detection in human diseases (Goodkind and Edwards, 2005), ecotoxicology test (Regier et al, 2013), assessing ripening stages in grape (Agudelo- Romero et al, 2013) and monitoring tools such as monitoring carbon dioxide injury in apple during storage (Yang et al, 2011;Gapper et al, 2013). Hence using the above ideas, we further analysed the expression profiles of three selected transcripts in root, leaf, stem, and meristem tissues of 9-month old oil palm plantlets that were predefined as PT and PS to G. boninense.…”
Section: Potential Transcripts Expression By Rt-qpcrmentioning
confidence: 99%
“…Numerous studies have demonstrated that mRNA abundance profiles of two or more contrast conditions or biological states can be potentially developed as biomarkers (Riedmaier and Pfaffl, 2013) for early detection in human diseases (Goodkind and Edwards, 2005), ecotoxicology test (Regier et al, 2013), assessing ripening stages in grape (Agudelo- Romero et al, 2013) and monitoring tools such as monitoring carbon dioxide injury in apple during storage (Yang et al, 2011;Gapper et al, 2013). Hence using the above ideas, we further analysed the expression profiles of three selected transcripts in root, leaf, stem, and meristem tissues of 9-month old oil palm plantlets that were predefined as PT and PS to G. boninense.…”
Section: Potential Transcripts Expression By Rt-qpcrmentioning
confidence: 99%